Manipulation impacts of jack mackerel meal in low fish meal diets on growth, feed availability, and biochemical composition of olive flounder (Paralichthys olivaceus) and economic analysis - Yu Jin Sim; Sung Hwoan Cho; Taeho Kim (Journal of the World Aquaculture Society, 2025)
Abstract Manipulation effects of jack mackerel meal (JMM) in the low fish meal (FM) diets substituting 50% FM with meat meal (MM) on growth performance of olive flounder and economic analysis were determined. Seven experimental diets were created. The control (Con) diet contained 60% FM. In the other diets, 50% of the FM level used for the Con diet was substituted with MM, and then graded levels (0, 10, 20, 30, 40, and 50%) of JMM were included at the expense of FM, named the MJ0, MJ10, MJ20, MJ30, MJ40, and MJ50 diets, respectively. The experimental diets were distributed to triplicate groups of fish. A total of 525 fish was divided into 21 flow‐through tanks. Fish were hand‐fed to apparent satiation for 8 weeks. Weight gain, specific growth rate (SGR), and feed consumption of fish fed the Con diet were comparable with fish fed the MJ20, MJ30, MJ40, and MJ50 diets. Weight gain, SGR, and feed consumption of fish linearly improved with JMM inclusion levels in the low FM diets replacing 50% FM with MM. The strong correlation between isoleucine and lysine content among essential amino acids in the experimental diets versus weight gain, SGR, and feed consumption of olive flounder were observed. Dietary treatments did not influence feed utilization, chemical composition, and amino acid profiles of fish. Incorporated 20%–50% JMM as an effective feed attractant and enhancer in the low FM diets replacing 50% FM with MM achieved comparable weight gain, SGR, and feed consumption to fish fed a 60% FM‐based diet. Finally, the MJ50 diet led to the highest economic profit index (EPI) for farmers.